Teorija in praksa, pravo in življenje: Liber amicorum Etelka Korpič-Horvat - Senčur Peček, Darja (2018)
Theory and practice, Law and Life: Liber amicorum Etelka Korpič-Horvat. The monograph, which consists of twenty-four scientific and professional contributions, is dedicated to the anniversary of dr. Etelka Korpič - Horvat. The authors of contributions are Slovenian and foreign experts with professional and/or friendly links to the honoree. The first part of the monograph contains contributions marked by a personal touch, which accentuate the honoree's contribution in various fields of her professional and social endeavours. The second part contains alphabetically sorted scientific contributions from the fields related to the honoree's research and professional work. Most of them are connected to the field of labour and social law, which was the most frequent subject of doc. dr. Etelka Korpič - Horvat's scientific-research activities. They address current issues in the field of individual and collective labour law, as well as social security law, in national, comparative and international contexts. The remaining contributions relate either to the role and decisions of the Constitutional Court of the Republic of Slovenia, of which the honoree is a judge and vice-president, to other issues related to the functioning of the state and its institutions or to legal issues related to the honoree's home region, Prekmurje.
Keywords: Etelka Korpič - Horvat; labour law; social security; Constitutional Court of the Republic of Slovenia; Faculty of Law of the University of Maribor; Prekmurje